Survival and Functional Status After Bridge-to-Transplant with a Left Ventricular Assist Device. Issue 7 (September 2019) - Suarez-Pierre, Alejandro; Zhou, Xun; Fraser, Charles D.; Grimm, Joshua C.; Crawford, Todd C.; Lui, Cecillia; Valero, Vicente; Choi, Chun W.; Higgins, Robert S.; Kilic, Ahmet
Abstract : The use left ventricular assist devices (LVAD) as a bridge-to-transplant (BTT) has become a common modality to treat end-stage heart failure. We sought to examine the impact of BTT on long-term survival and quality of life after heart transplant. The population was all adult patients undergoing isolated heart transplantation in the United States between 2007 and 2017. Inclusion criteria covered BTT patients with a LVAD (only Heartmate II [HMII] or HeartWare Ventricular Assist System [HVAD]) and compared these with patients undergoing de novo heart transplantation. Our primary end-point was survival at 1, 2, and 5 years. Secondary end-points were functional status, return to work, and rates of hospital readmission and graft rejection. Unconditional and conditional survival was estimated with the Kaplan-Meier method. The independent influence of BTT on risk-adjusted mortality was determined using Cox proportional hazards models. In this period, 5, 584 patients were bridged with an LVAD and 12, 295 underwent de novo transplantation. Unconditional survival was 2% higher in de novo patients at 1, 2, and 5 years. After risk adjustment, BTT was associated with increased mortality at each time point. Unadjusted 5 year survival, conditional on 90 day survival, was similar between groups (82.6% vs. 83.4%; p = 0.15). Functional status, return to work, and unadjusted rates of hospital readmission and graft rejection were similar at 1, 2, 5 years. Bridge-to-transplant with LVADs provides excellent survival and similar quality of life to that of patients undergoing de novo heart transplantation. Bridge-to-transplant patients experience a slightly higher mortality rate within 90 days of transplantation. Abstract : Supplemental Digital Content is available in the text.